Clinical Overview and Treatment of Hypokalemia in Pediatric Patients: A Narrative Literature Review - Winda Fauti (HM Publisher, 2023)
Hypokalemia is a condition in which the blood potassium levels are below the normal range, which is typically between 3.5 and 5.0 mEq/L. Potassium is an essential electrolyte that plays a critical role in many physiological processes in the body, including nerve and muscle function, heart rhythm, and acid-base balance. This literature review aimed to describe the clinical and current management aspects of hypokalemia in pediatric patients. The pathophysiology of hypokalemia involves a disturbance in the balance of potassium in the body, which can occur due to several mechanisms, including reduced intake of potassium-rich foods, increased loss of potassium, and redistribution of potassium. In children, clinical symptoms of hypokalemia may include weakness and fatigue, abdominal discomfort, cardiac symptoms, respiratory symptoms, neurological symptoms, polyuria, and renal symptoms. There are several diseases and conditions that can cause hypokalemia in children, including renal tubular acidosis, prolonged diarrhea, cystic fibrosis, hyperaldosteronism, malnutrition, medication, type 1 Bartter syndrome, type 2 Bartter syndrome, and Liddle syndrome. Some options for hypokalemia treatment are potassium supplements, a potassium-rich diet, intravenous potassium, and treating underlying conditions. In conclusion, hypokalemia is an overview of the underlying disease and requires immediate management. Understanding the pathophysiology of hypokalemia will increase the accuracy of diagnosis and accelerate hypokalemia intervention in children, as well as prevent complications due to hypokalemia.